Food-specific IgG Antibody Levels in Indian Subjects: A Retrospective Analytical Study - Shailesh Desai; Moumita Misra; Raj Jatale; Alap Christy; Shibani Ramchandran (Indian Journal of Medical Biochemistry)
Background: Many adverse food reactions have shown association with the presence of food-specific IgG antibodies in human serum. However, testing for such antibodies for diagnosis of adverse food reactions remains controversial. This study aimed was to understand the significance of food-specific IgG antibodies among patients who presented with food-dependent gastrointestinal symptoms viz upset stomach, bloating, etc. Materials and methods: A total of 2,748 cases who underwent testing for specific IgGs for 200+ food items under the ‘food intolerance test’ over 3 years from Jan 2020 to Dec 2022 across different Indian geographical regions were included in the study. The microarray food IgG assay was used to measure over 215 types of food-specific serum IgG antibodies, with the top 25 most common food IgGs found based on the biological reference interval further analyzed. Results: Barley (98.70%), pea (96.70%), sheep milk (87.20%), and cow milk (86.40%) were found to be the most prevalent food IgG antibodies. Corn maize, goat milk, cashew nut, pistachio, potato, soya bean, wheat, peanut, and hazelnut were found to be significantly associated with gender. Intolerance to cashew nuts, pistachio, potato, peanut and hazelnut was found to be significantly higher in females than males, whereas only corn maize was found to be significantly higher in males than female. Except for sunflower seed (p = 0.0551) all the other 24 food IgG concentrations showed a significant relation with age-group. Intra-group correlation among 25 food items showed a positive correlation between milk (cow) and casein (r = 0.919), pea and cola nut (r = 0.721), cashew nut, and pistachio (r = 0.753). The food intolerance seen in the study was mainly for vegetarian food. Conclusion: The study emphasizes the role of testing food-specific IgG antibodies in adverse food reactions which may further help in the diagnosis, management, and treatment of patients presenting with food-related gastrointestinal symptoms.